The Role of Principal Leadership in Improving the Quality of Students at SDN 1 Reco, Wonosobo Regency - Ida Dwi Astuti; Nurodin Usman (Prosiding University Research Colloquium, 2021)
A leader plays an important role in achieving the success and goals of an organization, aswell as school principals who have an important role in achieving educational and learninggoals. In leading the principal must have professionalism in order to achieve educationalgoals, therefore the principal must play a role in the process of planning, monitoring, etc.Improving the quality of schools is one of the goals to be achieved, so to improve the qualityof the institution itself, the principal must be able to foster and direct teachers to workprofessionally to improve the quality of students. This study aims to determine theprincipal's efforts or strategies in improving the quality of students at SDN 1 Reco,Wonosobo district. The research approach used is qualitative research with data collectiontechniques in the form of direct interviews with related sources, namely the principal ofSDN 1 Reco, Wonosobo Regency. The results showed that the principal acts as a manager,innovator, motivator by carrying out several efforts to improve the quality of students atSDN 1 Reco, Wonosobo Regency, namely trying to realize what is the school's vision andmission, realizing active, effective and efficient learning, generating interest and studentlearning motivation as well as trying to improve the character and moral values ofstudents.